Selective and fast oxidation of alcohol to aldehyde using novel catalytic deep eutectic solvent surfactants - Shokr Chalaki, Bahareh; Azizi, Najmedin; Mirjafary, Zohreh; Saeidian, Hamid (Frontiers in Chemistry, 2024)
Deep eutectic solvent (DES) has been considered as a useful catalyst and reaction medium for various organic transformations. Herein, we report the catalytic application of novel deep eutectic solvent- based surfactant (DES surfactant) for the selective and fast oxidation of alcohols to aldehydes. The readily accessible DES surfactants (FeCl3/BHDC) was prepared using inexpensive ferric chloride (FeCl3) and benzyl hexadecyl dimethyl ammonium chloride in a simple manner. The synthesized FeCl3/BHDC was characterized using various techniques, including, FTIR spectroscopy, thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and energy- dispersive X-ray spectroscopy (EDS) to determine its structure. The catalytic activity of FeCl3/BHDC in the selective oxidation of various alcohols to corresponding aldehyde derivative was investigated. The results showed the reaction could be completed within very short reaction times ranging from 2 to 15 min, while achieving good to excellent yields. This protocol offers a facile strategy and excellent efficiency in selectively oxidizing various alcohol derivatives to their respective aldehydes and ketones, utilizing hydrogen peroxide in the presence of catalytic DES surfactant.